Grafting perylenes to ZnO nanoparticles - Schönamsgruber, Jörg; Zeininger, Lukas; Hirsch, Andreas (Chemistry - A European Journal, 2014)
A new prototype of dendritic perylenes suitable for the chemical functionalization of inorganic nanoparticles was synthesized and characterized. The bay-functionalized perylene core of these molecular architectures was coupled to a catechol moiety, which serves as an anchor group for the functionalization of metal oxides, in particular ZnO. To increase the solubility of both the perylene and the targeted hybrid nanostructures, a Newkome-type dendron bearing nine positive charges was introduced. This charge was also employed to stabilize the nanoparticles and further protect them from Ostwald ripening through Coulombic repulsion. ZnO quantum dots with an average diameter of 5nm were synthesized and functionalized with the perylene derivative. Successful functionalization was clearly demonstrated by dynamic light scattering, zeta-potential measurements, thermogravimetric analysis/MS, and UV/Vis and fluorescence spectroscopy. The generated particle dispersions were stable against agglomeration for more than eight weeks. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.